2021
DOI: 10.1108/lthe-09-2021-0087
|View full text |Cite
|
Sign up to set email alerts
|

The development of Emirati university students' intercultural sensitivity

Abstract: PurposeThis study investigated the effects of an intercultural communication (IC) course on Emirati university students' intercultural sensitivity (IS).Design/methodology/approachThe participants were 89 Emirati students. The course required student involvement in a variety of tasks and activities, both inside and outside the classroom. The development of the students' IS was tracked using two instruments: the Intercultural Sensitivity Scale (ISS) and a reflective writing task.FindingsThe difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Participants reported daily knowledge improvements as well as improved cross‐cultural communication skills. Our observations are consistent with Feng and Byram (2006) who report that cross‐cultural programmes are dynamic processes of interaction, enhancing learners' knowledge levels, largely as a result of an active learning process (Deveci et al, 2021). In such experiences, learners engage in extensive reading and reflection on intercultural concepts and ideas, “merging” academic knowledge with experiences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants reported daily knowledge improvements as well as improved cross‐cultural communication skills. Our observations are consistent with Feng and Byram (2006) who report that cross‐cultural programmes are dynamic processes of interaction, enhancing learners' knowledge levels, largely as a result of an active learning process (Deveci et al, 2021). In such experiences, learners engage in extensive reading and reflection on intercultural concepts and ideas, “merging” academic knowledge with experiences.…”
Section: Discussionsupporting
confidence: 92%
“…We observed how such engagements featured enjoyment and satisfaction. Improved self‐confidence in the context of cultural diversity is also an observation that Deveci et al (2021) reported. Participants' engagement with interactions in cross‐cultural contexts reflects individuals' propensity to initiate communication with individuals who are culturally diverse and distinct.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, an expatriate's positive perception of cultural differences may help them adapt-building stronger bonds and understanding with locals-which improves their productivity at work (Bhardwaj, 2022). According to Deveci et al (2022), there is a strong and positive correlation between cultural sensitivity and job performance, making it an essential personal attribute for expats to have in order to perform well at work. Simoni, et al (2020) found a positive correlation between an expatriate's work performance and cross-cultural adjustment in a similar setting.…”
Section: Cultural Sensitivity Training and Expatriate Performancementioning
confidence: 99%
“…In this context, EFL graduates who possess a good command of English can have advantages in future employment. Since exchanging ideas and information is the main purpose of language (Deveci et al, 2021;Koch & Takashima, 2021;Vieluf & Göbel, 2019), the main goal of English language teaching (ELT) is evidently to assist students in improving their language skills and competence. Motivation to learn English, in this case, seems to be the key to any possible success or failure of difficult tasks, including acquiring language content (e.g.…”
Section: Introductionmentioning
confidence: 99%